A Computational Study of C–H Bond Abstraction in β-Amino Alcohols: O-side Activation over N-side via Boronate Adduct Formation - Sanosa, Nil; Gómez-Suárez, Adrián; Funes-Ardoiz, Ignacio (Synthesis, 2025)
A density functional theory (DFT) study was performed to evaluate the reaction mechanism underlying the chemoselective C–H abstraction in β-amino alcohols under a photoredox-catalyzed platform. Our results support a three-step mechanism based on the formation of a highly activated tetracoordinated boronate adduct followed by a selective hydrogen atom transfer (HAT) and a Giese-type radical addition, which together generate the experimentally observed γ-oxo-δ-amino esters. We demonstrated that α-hydroxy C–H bonds are more readily activated toward the HAT step than the α-amino C–H bond. This enhanced chemoselectivity arises from the tetracoordinated boronate adduct, which increases the hydridic character of the α-hydroxy H atom and lowers the bond dissociation enthalpy (BDE) of the C–H bond.
Keywords: Density functional theory; β-Amino alcohols; Chemoselectivity; Boron activation; Reaction mechanism; HAT